Differences in IL-1β and IL-6 levels in the gingival crevicular fluid during acute phase of orthodontic tooth movement between juveniles and young adults - Vujačić Amila; Konić Aleksandra; Pavlović Jasna; Todorović Vera; Vukićević Vladanka; Jevremović Danimir; Milošević-Jovčić Nadežda (Vojnosanitetski Pregled)
Background/Aim. There is little information, about the difference in cytokine levels in the gingival crevicular fluid (GCF) during orthodontic tooth movement (OTM), between juveniles (children) and young adults (adults). The aim of this study was to examine the levels of interleukins IL-1β and IL- 6 in GCF of these two age groups during the acute phase of OTM. Methods. The subjects, 10 children and 10 adults, underwent OTM of a single tooth, with an untreated antagonistic tooth used as the control group. GCF was sampled from both the control and treatment sites right before the beginning (the baseline) and 24 h, 72 h and 168 h upon initiation of OTM. Cytokine levels were determined by enzymelinked immunosorbent assay (ELISA). Results. The levels of both GCF IL-1β and IL-6 showed a bimodal peak during early phase of OTM, at 24 h and 168 h, in both age groups. As the statistic has shown, the increase in IL-1β levels was more prominent after 168 h in treated teeth of children, compared to both children’s control teeth and treated teeth of adults, whilst the GCF IL-6 levels in the same group increased significantly after 24 h, as well as after 168 h, approximately 70 and 55 fold, respectively. In the same time periods the increase of IL-6 levels in GCF of adults was notably lesser, averaging approximately 5 and 10 fold, respectively, compared to the control teeth. In addition, the amount of tooth movement was statistically larger for children than for adults 168 hours upon the initiation of OTM. Conclusion. GCF IL-1β and IL-6 were increasingly expressed during initial phase of OTM in both children and adults. However, excretory response of cytokines in children’s GCF, especially the concentration of IL-6, was at a significantly higher level than that of adults’, which accords to the finding that the initial OTM is faster in children.